The DNA-binding domain of the transcriptional activator protein NifA resides in its carboxy terminus, recognises the upstream activator sequences of nif promoters and can be separated from the positive control function of NifA. - Morett, E (1988)
The positive control protein NifA activates transcription of nitrogen fixation promoters in Klebsiella pneumoniae. NifA is believed to bind to specific sites, the upstream activator sequences (UAS's), of the nif promoters which it activates. We have now shown by mutation of the carboxy terminus of NifA that this is the DNA-binding domain and that the DNA-binding and positive activator functions of NifA can be separated. Mutational analysis of the nifH UAS and in vivo methylation protection analysis of the interaction of NifA with the nifH promoter demonstrates that the UAS is recognised by the carboxy terminus of NifA. The UAS's of K. pneumoniae nif promoters are also required for activation by the Rhizobium meliloti NifA indicating that this activator also possesses DNA-binding activity.